Exploring the ripples of the 2018 organ allocation policy change. Issue 7 (21st March 2022) - Blitzer, David; Copeland, Hannah
Abstract: In this issue of the Journal, Patel et al. analyzed the United Network of Organ Sharing database for the impact of the 2018 organ allocation policy changes on outcomes for patients based on BMI. Their work is important for highlighting a population at risk of bias and emphasizes the need for continued study of the ripple effect of the allocation policy changes.